Body composition and phase angle as an indicator of nutritional status in children with juvenile idiopathic arthritis - Paweł Więch; Izabela Sałacińska; Dariusz Bazaliński; Mariusz Dąbrowski (BMC, 2018)
Abstract Background Juvenile idiopathic arthritis (JIA) is the most common chronic, systemic autoimmune connective tissue disease diagnosed in children and adolescents. An important aspect of monitoring of children with JIA is a precise assessment of the nutritional status to identify children and adolescents at risk of malnutrition. The aim of the study was to assess the body composition and phase angle in children diagnosed with JIA in comparison to age and sex matched healthy children since there are scarce reports in paediatric patients. Methods A total of 46 children and adolescents aged 4-18 years, with JIA were included in the cross-sectional study. Controls were selected from the group of healthy children and adolescents. Children with diagnosed JIA and healthy children were strictly matched for age and gender. In both groups BIA with phase angle calculation was performed. Results Phase angle score was significantly lower in the study group compared to control group (5.45 ± 0.64 vs. 5.85 ± 0.80, p = 0.010). Also lower percentage of body cell mass (50.63 ± 3.46 vs. 52.70 ± 4.06, p = 0.010) and muscle mass (46.02 ± 6.32 vs. 49.53 ± 6.67, p = 0.005) were revealed. In the analysis of subtypes of JIA we found significant differences between children and adolescents with polyarthritis compared to control group, while no significant differences were found between patients with oligoarthritis and control group. Conclusions The obtained results indicate a higher risk of malnutrition in children and adolescents with JIA compared to healthy peers, predominantly in patients with polyarthritis.